2021
DOI: 10.1186/s40348-021-00118-8
|View full text |Cite|
|
Sign up to set email alerts
|

Novel ways to monitor immunosuppression in pediatric kidney transplant recipients—underlying concepts and emerging data

Abstract: After pediatric kidney transplantation, immunosuppressive therapy is given to avoid acute and chronic rejections. However, the immunosuppression causes an increased risk of severe viral complications and bacterial infections and is associated with serious side effects. It is therefore crucial to achieve the optimal individual balance between over- and under-immunosuppression and thereby avoid unnecessary exposure to immunosuppressive drugs. In routine use, steering of immunosuppressants is performed primarily … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…The selection of these predictive indicators and the establishment of cutoff values are valuable for understanding the risk factors associated with irAEs. These findings can assist clinicians in optimizing treatment strategies and implementing appropriate monitoring and management protocols for patients undergoing immunotherapy [ 30 , 31 ]. By adopting a more individualized approach to therapy, balancing the potential benefits of ICIs with the risks of developing irAEs becomes possible.…”
Section: Discussionmentioning
confidence: 99%
“…The selection of these predictive indicators and the establishment of cutoff values are valuable for understanding the risk factors associated with irAEs. These findings can assist clinicians in optimizing treatment strategies and implementing appropriate monitoring and management protocols for patients undergoing immunotherapy [ 30 , 31 ]. By adopting a more individualized approach to therapy, balancing the potential benefits of ICIs with the risks of developing irAEs becomes possible.…”
Section: Discussionmentioning
confidence: 99%
“…The selection of these predictive indicators and the establishment of cutoff values are valuable for understanding the risk factors associated with irAEs. These ndings can assist clinicians in optimizing treatment strategies and implementing appropriate monitoring and management protocols for patients undergoing immunotherapy [25,26]. By adopting a more individualized approach to therapy, balancing the potential bene ts of ICIs with the risks of developing irAEs becomes possible It is important to acknowledge the limitations of this study.…”
Section: Discussionmentioning
confidence: 99%
“…26,27 Due to the natural non-pathogenicity and immune function monitoring properties of TTV, there has been an increasing interest in the potential use of TTV DNA load as a novel functional marker of immune status. 5,[28][29][30][31] TTV DNA load increased rapidly from Days 7 to 30, peaked 3−12 months after KT, and then decreased gradually. 18,19,[32][33][34] Previous studies suggested a potential of TTV quantification for risk prediction of infectious diseases and rejection events in KT recipients.…”
Section: Introductionmentioning
confidence: 97%
“…Of note, the virus is unaffected by conventional antiviral drugs 17,25 and inversely correlated with the number and function of T‐lymphocytes 26,27 . Due to the natural non‐pathogenicity and immune function monitoring properties of TTV, there has been an increasing interest in the potential use of TTV DNA load as a novel functional marker of immune status 5,28–31 …”
Section: Introductionmentioning
confidence: 99%